Collection of developmental history in the evaluation of schizophrenia spectrum disorders - Reiersen, Angela Michelle (Scandinavian Journal of Child and Adolescent Psychiatry and Psychology, 2016)
Background: Schizophrenia is a heterogeneous disorder that is characterized by varying levels of hallucinations, delusions, negative symptoms, and disorganized features. The presence and severity of neurodevelopmental precursors and premorbid psychopathology also vary among individuals. To fully understand individual patients and to sort out phenotypic heterogeneity for genetic research studies, instruments designed to collect developmental history relevant to schizophrenia may be helpful.Objective: The goal was to describe a pair of self-report and parent-report instruments developed for the purpose of collecting the developmental history of patients with known or suspected schizophrenia spectrum disorders.Method: Two developmental history instruments were designed for use in studies of brain morphology and cognition in schizophrenia probands and their unaffected siblings. The instruments focus mainly on motor abnormalities and other features that have been described as schizophrenia precursors.Results: The Motor Skills History Form is a brief self-report form that asks about patients’ childhood and adolescent motor abilities as well as their current motor functioning. The Developmental & Motor History Form is a more detailed parent-rated form that covers aspects of patients’ early (infant/preschool) development; their childhood and adolescent motor abilities; any childhood behaviors that may be related to later psychosis risk; and their history of any neurological, emotional, or cognitive disorders diagnosed during childhood or adolescence. The instruments can be used either for interviews or as self-administered questionnaires. The parent-rated form has been used for research and for the clinical assessment of children and adolescents with complex neurodevelopmental presentations with or without strong evidence of schizophrenia risk.Conclusions: The collection of developmental history information is important when evaluating individuals with schizophrenia and related disorders. The Motor Skills History Form and the Developmental & Motor History Form can be used to collect this information for clinical evaluation or research purposes.